REVIEW STUDY ON ANALYSIS OF THE SOLUBILITY OF BIOPHARMACEUTICAL CLASSIFICATION SYSTEM CLASS II DRUGS IN A SELF-EMULSIFYING DRUG DELIVERY SYSTEM - DEVENDRA SINGH LODHI,; AAKASH SINGH PANWAR,; NIRMAL DONGRE, (Asian Journal of Pharmaceutical and Clinical Research, 2022)
By dissolving drug molecules in these solutions, a unit dosage form for oral administration can be generated for oral administration. Self-emulsifying drug delivery system (SEDDS) is utilized to address the inadequate bioavailability of poorly soluble and highly permeable drugs, according to the literature. These methods can disseminate and deliver hydrophobic medications as a unit dose form for oral administration in this fashion. SEDDS formulations self-emulsify (micro/nano) after being discharged into the intestinal lumen and coming into contact with the gastrointestinal (GI) fluid. Several factors must be considered to make the oral drug administration difficult, including poor water solubility and limited permeability. Self-emulsifying drug delivery can increase the solubility of biopharmaceutical classification system (BCS) II medicines. The SEDDS is a drug delivery system that enhances the solubility of lipophilic medications. It has risen in popularity over time. Under moderate agitation and subsequent dilution, GI fluids are categorized as hydrophilic liquid mixes that are isotropic. This research looks at a variety of uses as well as recent advancements in SEDDS composition, evaluation, dosage forms, and novel techniques to convert liquid SEDDS to solids. Final Thoughts Determining whether or not it is feasible to construct a BCS Category 2 medication formulation based on SEDDS represents a significant contribution of this effort. Medicines with solubility issues and low and variable bioavailability will benefit from the connected technologies.